2002
DOI: 10.1038/sj.mp.4001036
|View full text |Cite
|
Sign up to set email alerts
|

Early maternal deprivation reduces the expression of BDNF and NMDA receptor subunits in rat hippocampus

Abstract: It is well accepted that events that interfere with the normal program of neuronal differentiation and brain maturation may be relevant for the etiology of psychiatric disorders, setting the stage for synaptic disorganization that becomes functional later in life. In order to investigate molecular determinants for these events, we examined the modulation of the neurotrophin brain-derived neurotrophic factor (BDNF) and the glutamate NMDA receptor following 24 h maternal separation (MD) on postnatal day 9. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
240
3
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(268 citation statements)
references
References 57 publications
14
240
3
11
Order By: Relevance
“…We find that different durations of a single MS episode result in increased BDNF III mRNA (3 h MS) or a decline in BDNF I expression (6 h MS) in all hippocampal subfields. However, neither total BDNF (V) nor CREB expression is altered by a single episode of MS. A previous study (Roceri et al, 2002) with an acute 24 h MS reported no alterations in total BDNF levels in postnatal life, but resulted in a decline in BDNF expression in the adult hippocampus. Although short duration MS may have an adaptive influence on BDNF splice variants, single MS for long durations appears to cause maladaptive changes in BDNF, and this is likely to reflect both the effects of separation per se, as well as disrupted nutritional support and thermal regulation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We find that different durations of a single MS episode result in increased BDNF III mRNA (3 h MS) or a decline in BDNF I expression (6 h MS) in all hippocampal subfields. However, neither total BDNF (V) nor CREB expression is altered by a single episode of MS. A previous study (Roceri et al, 2002) with an acute 24 h MS reported no alterations in total BDNF levels in postnatal life, but resulted in a decline in BDNF expression in the adult hippocampus. Although short duration MS may have an adaptive influence on BDNF splice variants, single MS for long durations appears to cause maladaptive changes in BDNF, and this is likely to reflect both the effects of separation per se, as well as disrupted nutritional support and thermal regulation.…”
Section: Discussionmentioning
confidence: 79%
“…Although the effects of MS on total BDNF expression (exon V) have been examined (Greisen et al, 2005;Roceri et al, 2002Roceri et al, , 2004, there is no information at present on the regulation of specific BDNF transcripts or the region specificity of changes in BDNF within hippocampal subfields. We find that different durations of a single MS episode result in increased BDNF III mRNA (3 h MS) or a decline in BDNF I expression (6 h MS) in all hippocampal subfields.…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, a 24 h period of maternal separation leads to the emergence of a depressive-like phenotype and subnormal hippocampal BDNF expression later in adult life, as well as attenuated stress-induced BDNF alterations. 28 This suggests that a predisposition to depression caused by an early developmental insult may be mediated by a persistent impairment of the BDNF signalling pathway.…”
Section: Preclinical Evidencementioning
confidence: 99%
“…It has been shown that maternal care can increase hippocampal NMDAR levels, resulting in elevated BDNF expression and increased hippocampal synaptogenesis and neuronal survival, and thus enhanced spatial learning and memory in adulthood (Liu et al, 2000;Bredy et al, 2003). Conversely, prolonged maternal separation during the early postnatal period is associated with evidence for increased apoptosis, decreased neurotrophic factor expression, and reduced mossy fiber density in adulthood (Lee et al, 2001;Huot et al, 2002;Roceri et al, 2002). Our study extends these observations by showing that rats exposed to an appropriate bout of maternal separation are able to delay the developmental decline of LFS-LTD induction.…”
Section: Discussionmentioning
confidence: 99%